A very Marley Christmas - Grogan, John, 1957-; Cowdrey, Richard (New York : HarperCollinsPublishers, 2008)
Marley the rambunctious puppy and his family prepare for Christmas, hoping very much for snow.
3.5
K-3
Keywords: Dogs -- Juvenile fiction; Christmas -- Juvenile fiction; Dogs -- Fiction; Christmas -- Fiction; Dogs -- Fiction; Christmas -- Fiction